Comparison of the relative diagnostic performance of 68Ga-DOTA-IBA and 18F-NaF for the detection of bone metastasis - Deng, Jia; Yang, Jian; Wang, Yingwei; Liu, Guangfu; Chen, Yue (Frontiers in Oncology, 2024)
Purpose: We aimed to compare the relative diagnostic efficacy of 68Ga-Labeled DOTA-ibandronic acid (68Ga-DOTA-IBA) to that of 18F-NaF PET/CT as a mean of detecting bone metastases in patients with a range of cancer types. Methods: This study retrospectively enrolled patients with bone metastases associated with various underlying malignancies. Histopathology and follow-up CT or MRI imaging results were used as reference criteria, with a minimum follow-up period of 3 months. The SUVmax and number of bone metastases were recorded. TBR was calculated along with the detection rate, sensitivity, specificity, PPV, NPV, and accuracy of 68Ga-DOTA-IBA and 18F-NaF PET/CT imaging for overall and partial primary solid tumor bone metastases. Pearson chi-square test, McNemar test, and Kappa test was conducted to assess the correlation and consistency of diagnostic efficiency between the two imaging agents. ROC curve was performed to compare diagnostic performance. Differences in SUVmax and TBR values between the two imaging agents were analyzed using the Wilcoxon test. The difference was statistically significant when P < 0.05. Results: A total of 24 patients (13 women and 11 men) were included in this study, with a mean age of 52 (interquartile range, 49-64 years). There was no significant difference between the two imaging methods (P < 0.01), and there was a significant correlation (X2=168.43, P < 0.001) and a strong consistency (Kappa=0.774,P < 0.001) between the two imaging agents. The SUVmax values of lesions measured by 68Ga-DOTA-IBA and 18F-NaF imaging in 22 patients with bone metastasis were 5.1±5.4 and 19.6±15.1, respectively, with statistically significant differences (P＜0.05). The TBR values of the two imaging methods were 5.0±5.0 and 6.7±6.4, respectively, with statistically significant differences (P＜0.05). The AUC of the SUVmax of 68Ga-DOTA-IBA and 18F-NaF curves were 0.824 and 0.862, respectively, with no statistically significant difference (P=0.490). No significant difference was found in the AUC of the TBR of 68Ga-DOTA-IBA and 18F-NaF (0.832 vs 0.890; P=0.248). Conclusion: The diagnostic efficacy of 68Ga-DOTA-IBA for bone metastasis lesions is comparable to that of 18F-NaF. This finding holds significant clinical importance in terms of diagnosis of bone metastasis and selecting treatment plans for patients with malignant tumors.